Bicolor Bessel beams generator based on single-mode fiber for STED system light source - Shao Luqing; Li Xijun; Qiu Min (EPJ Web of Conferences)
In this paper, we have presented a novel and compact bicolor Bessel beams (bi-BBs) generator based on a single-mode fiber integrated with an axicon-like microstructure (AM). The proposed design utilized two Bessel beams manifested as pump beam of circular distribution at λ=405 nm and STED beam of donut distribution at λ=532 nm. Through numerical simulations, the influence of the AM size variance on the characteristics of bi-BBs was investigated and a type of AMs has been found to support STED beam. By controlling and optimizing the characteristics of bi-BBs emitted from a single-mode fiber greatly reduces the coaxial alignment difficulty of the free space STED systems and provides a new way to achieve mirrorless STED super-resolution systems.